A Capabilities-based Gender Equality Policy for Higher Education: Conceptual and Methodological Considerations. Issue 2 (2nd April 2016) - Loots, Sonja; Walker, Melanie
Abstract: The complex transformative intent of policy goals is often marginalized in favour of tangible, measurable outcomes. Such a pattern is evident in the tracking of global social justice goals, such as gender equality, where sole reliance on numerical parity data to track progress has led to the simplification of the concept for the sake of measurement. This intensifies the need to focus both on conceptual and methodological considerations in policy development and evaluation to enhance human development and promote the transformation of inequalities towards social justice. Through reporting on a mixed-methods process to inform and develop a capabilities-based gender equality policy at a South African university, the paper asks what gender equality should look like conceptually, and identifies empirically valued functionings and capabilities which could act as transformative policy evaluation indicators. The paper reports on diverse student data from 57 qualitative interviews and 843 survey respondents, which indicate differences between what social groups value and where interventions are needed. The paper suggests that the capabilities approach could be an important evidence-based policy driver in higher education, with the possibility to combine both a rich conceptual approach and methodological considerations in operationalization so that social justice goals and outcomes result.